Dc arc detection and interruption in photovoltaic power systems - Cheah, Yi Min (2023)
This project focuses on the design and fabrication of a reliable and safe direct current (DC) arc generator for DC arc fault testing in photovoltaic (PV) systems. The project aims to evaluate the effectiveness of the DC arc fault protection features in the Huawei Solar Inverter SUN2000-2KTL-L1 through various tests including arc fault circuit interrupter (AFCI), insulation resistance (RISO) monitoring, residual current monitoring (RCD), and rapid shutdown. The tests were conducted under real-world conditions using an on-site PV system. The results demonstrate the effectiveness of the Huawei Solar Inverter in mitigating the risks associated with DC arc faults, including the prevention of fires caused by DC series arc faults, protecting against electrical shocks caused by dc arc fault and ensuring system safety and reliability by monitoring insulation resistance before the DC circuit is completed. The rapid shutdown feature allows for the safe and swift shutdown of the PV system, reducing the risk of damage or injury. The project contributes to the development of DC arc fault protection in the PV industry and provides valuable insights into the capabilities of the Huawei Solar Inverter SUN2000-2KTL-L1 in handling DC arc faults, ensuring the safety and reliability of PV systems.